Dissatisfaction with dentofacial appearance and the normative need for orthodontic treatment: determinant factors - Anderson Barbosa de Almeida; Isabel Cristina Gonçalves Leite; Camilo Aquino Melgaço; Leandro Silva Marques (Dental Press Editora, 2014)
OBJECTIVE: This study aims at assessing the normative need for orthodontic treatment and the factors that determine the subjective impact of malocclusion on 12-year-old Brazilian school children. METHODS: A total of 451 subjects (215 males and 236 females) were randomly selected from private and public schools of Juiz de Fora, Brazil. The collected data included sociodemographic information and occlusal conditions. The esthetic subjective impact of malocclusion was assessed by means of the Orthodontic Aesthetic Subjective Impact Score - OASIS, whereas the malocclusion and the need for orthodontic treatment were assessed by means of the Dental Aesthetic Index (DAI) and the Index of Orthodontic Treatment Need-Aesthetic Component (IOTN-AC). RESULTS: Prevalence of normative need for orthodontic treatment was 65.6% (n = 155), and prevalence of orthodontic esthetic subjective impact was 14.9%. The following variables showed significant association with esthetic subjective impact of malocclusion: female (p = 0.042; OR = 0.5; CI = 0.2-0.9), public school student (p = 0.002; OR = 6.8; CI = 1.9-23.8), maxillary overjet ≥ 4 mm (p = 0.037; OR = 1.7; CI = 1-3) and gingival smile ≥ 4 mm (p = 0.008; OR = 3.4; CI = 1.3-8.8). CONCLUSION: The normative need for orthodontic treatment overestimated the perceived need. Occlusal and sociocultural factors influenced the dissatisfaction of schoolchildren with their dentofacial appearance.